Engaging Students with a Mobile Game-Based Learning System in University Education - Bartel, Alexander; Hagel, Georg (International Journal of Interactive Mobile Technologies (iJIM), 2014)
In this contribution we present a game-based learning concept which is based on mobile devices. It focuses a joyful stabilization of knowledge and the engagement of students using the Gamification approach and its game mechanics. Previous findings how to promote students’ motivation are adapted in the mobile context and discussed. A pre-evaluation of the prototype is described with its findings.